العذاب النفسي في القرآن الكريم - حشيفة, كوثر; بوتة, حياة (University Of Eloud جامعة الوادي, 2019)
"الملخص: تناولت هذه الدراسة موضوع ""العذاب النفسي في القرآن الكريم -دراسة موضوعية-"" نظرا لأهمية الموضوع في إثبات نوع من أنواع العذاب في القرآن الكريم، وهو العذاب النفسي على المؤمنين والكافرين والمنافقين، ولما في هذا الموضوع من أثر على النفس من وقع عليه العذاب، وكل من سمعه، اقتضت دراستنا البحث عن النصوص القرآنية تحمل في طياتها حقيقة العذاب النفسي وأثره، كما أننا تناولنا العلاج لهذا العذاب النفسي على المؤمنين من خلال التصور القرآني الفريد في علاج من ابتلي به، حيث إن القرآن يتميز بأسلوبه التربوي الفريد في تربية النفس البشرية، لتفر إلى بارئها وخالقها، وترد إليه ردا جميلا، ولقد حرصنا في بحثنا هذا على بيان هذا النوع من العذاب ووصف حالة من يصيبه هذا العذاب، ولقد شمل هذا البحث على ثلاث مباحث، مبحث تمهيدي بعنوان: مفهوم العذاب النفسي في القرآن الكريم، والمبحث الأول: العذاب النفسي على المؤمنين وعلاجه في القرآن الكريم، وأما بالنسبة للمبحث الثاني فقد كان بعنوان: العذاب النفسي على الكافرين والمنافقين في القرآن الكريم. ثم الخاتمة وفيها أبرز النتائج التي خلُص إليها البحث ومن أهمها: أن العذاب النفسي أشد ألما من العذاب الجسمي, لما يتركه من أثر في النفس, كما أنه يسبق العذاب الجسمي. Abstract: This study dealt with the subject of ""psychological torment in the Holy Quran - objective study -"" in view of the importance of the subject in proving a kind of torment in the Holy Quran, the psychological torment on the believers and unbelievers and hypocrites, and in this subject of the impact on the self who inflicted the torment, Of his hearing, Our study necessitated the search for Qur'anic texts carrying the reality of psychological suffering and its impact. We also dealt with the treatment of this psychological torment on the believers through the unique Quranic perception in the treatment of those who suffer from it, as the Koran is characterized by its unique educational method in the education of the human psyche, to escape to its creator and creator, and respond to it beautifully. The kind of torment described as the condition of this torment The research included three topics: a preliminary study entitled: The concept of psychological torment in the Holy Quran, and the first topic: psychological torment on the believers and treatment in the Holy Quran. As for the second topic was entitled: psychological torment on the unbelievers and hypocrites in the Koran. Then the conclusion and the most prominent results of the research and the most important: that psychological torture is more painful than physical torment, because it leaves the impact and injury in the soul, as it precedes physical torment "
مذكرة ماستر تخصص تفسير علوم القرآن
Keywords: العذاب - النفسي - الكافرون - المنافقين; "Torment - psychological - unbelievers - hypocrites "